BIOM-50. GENETIC PREDISPOSITION TO LONGER TELOMERE LENGTH AND RISK OF CHILDHOOD, ADOLESCENT AND ADULT-ONSET EPENDYMOMA. (9th November 2020) - Zhang, Chenan; Ostrom, Quinn; Semmes, Eleanor; Ramaswamy, Vijay; Hansen, Helen; Morimoto, Libby; de Smith, Adam; Pekmezci, Melike; Vaksman, Zalman; Hakonarson, Hakon; Diskin, Sharon; Metayer, Catherine; et al.
Abstract: INTRODUCTION: Ependymoma is the third most common brain tumor in children, with well-described molecular characterization but poorly understood underlying germline risk factors. Telomerase reactivation in somatic cells has been linked to ependymoma progression, recurrence, and survival, and has been implicated as an important prognostic marker and potential therapeutic target. METHODS: To investigate whether inherited predisposition to longer telomere length influences ependymoma risk, we utilized case-control data from three studies: 1) a population-based pediatric and adolescent ependymoma case-control sample from California (153 cases, 696 controls), 2) a hospital-based pediatric posterior fossa type A ependymoma (EPN-PF-A) case-control study from Toronto's Hospital for Sick Children and the Children's Hospital of Philadelphia (83 cases, 332 controls), and 3) a multicenter adult-onset ependymoma case-control dataset nested within the Glioma International Case-Control Consortium (GICC) (103 cases, 3287 controls). We investigated the individual effect of telomere-length associated SNPs on ependymoma risk, as well as the combined effect of these SNPs through polygenic score and Mendelian randomization analyses. RESULTS: We observed an association between genetic predisposition to longer LTL and increased risk of adolescent-onset (P= 3.97x10 -3 ) and adult-onset (P =0.042) ependymoma, but not ependymoma diagnosed in children < 12 years old (P=0.21), or among the pediatric EPN-PF-A sample (P=0.59). Comparing ependymoma patients ages 12–19 to those under 12 years of age demonstrated that age significantly modified the association between longer telomere length and ependymoma risk (P=0.021). CONCLUSIONS: These findings complement emerging literature suggesting that dysregulated telomere maintenance is important for ependymoma pathogenesis and that longer telomere length is a risk factor for various neoplasms of the peripheral and central nervous system.